2019
DOI: 10.1016/j.ebiom.2018.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Targeting SET to restore PP2A activity disrupts an oncogenic CIP2A-feedforward loop and impairs triple negative breast cancer progression

Abstract: BackgroundTriple-negative breast cancer (TNBC) remains difficult to be targeted. SET and cancerous inhibitor of protein phosphatase 2A (CIP2A) are intrinsic protein-interacting inhibitors of protein phosphatase 2A (PP2A) and frequently overexpressed in cancers, whereas reactivating PP2A activity has been postulated as an anti-cancer strategy. Here we explored this strategy in TNBC.MethodsData from The Cancer Genome Atlas (TCGA) database was analyzed. TNBC cell lines were used for in vitro studies. Cell viabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 73 publications
2
33
0
Order By: Relevance
“…Consistent with the tumor suppressor role of PP2A, the PP2A inhibitors, inhibitor-2 of protein phosphatase-2A (SET) and cancerous inhibitor of PP2A (CIP2A), are overexpressed in a variety of cancers [122][123][124][125][126]. These proteins function to prevent PP2A-B subunits from binding the PP2A A-C core complex, decreasing global PP2A activity and contributing to therapeutic resistance [127,128].…”
Section: Indirect Protein Phosphatase 2a (Pp2a) Activationmentioning
confidence: 96%
“…Consistent with the tumor suppressor role of PP2A, the PP2A inhibitors, inhibitor-2 of protein phosphatase-2A (SET) and cancerous inhibitor of PP2A (CIP2A), are overexpressed in a variety of cancers [122][123][124][125][126]. These proteins function to prevent PP2A-B subunits from binding the PP2A A-C core complex, decreasing global PP2A activity and contributing to therapeutic resistance [127,128].…”
Section: Indirect Protein Phosphatase 2a (Pp2a) Activationmentioning
confidence: 96%
“…The authors of the Dupre et al [5], Lemmonier et al [9] and Dupre et al [139] completely ignored published works that contradicted their work and did not provide any reasons to the readers and Scientific Researchers who are trying to decipher who is/are telling the truth and whether to spend resources in man hours to try to repeat their published works that are at best misleading and at worse dishonest. The idea that a form of PP-2A could undergo marked inhibition during resumption of meiosis is not compatible with the known function of PP-2A as a key controller of cell transformation and as tumor suppressor [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100].…”
Section: Role Of Pp-2a In the Control Of Mitosismentioning
confidence: 99%
“…One or more form(s) of PP-2A in the cell has/have low basal activity upon entry into mitosis and becomes moderately activated prior to and exit of mitosis. As countless studies have shown, logically, extensive inhibition of PP2A would lead to cell transformation and tumorigenesis[85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100].The following model for the role of PP-1 and PP-2A in the control of mitosis that does not rest upon the conclusions of Mochida et al[1] and Gharbi-Ayashi et al[2] are a lot more realistic. The model takes in account the works of Mayer-Jackel et al[24,25], Hutchins et al[26], Peng et al[101,102], Margolis et al[27,115,116], Forrester et al[28], Wu et al[117], Tung et al[110,111,156], Puntoni and Villa-Moruzzi[152,153], Dohadwala et al[161], Kwon et al[162], Lamb et al[165], Brautigan et al[166], Fernandez et al[167], and Li et al[160], Model for the role of PP-2A in the control of meiosis.Role of PP-2A in the control of meiosis in Xenopus oocytes.…”
mentioning
confidence: 99%
“…In addition, the majority of the CIP2Aand PME-1-target peptides overlapped with the target peptides of SET 22 . Furthermore, targeting of SET with siRNA also down-regulates CIP2A 23 . Therefore, we hypothesised that SET might be the desired target molecule, if it is expressed in CTCs.…”
Section: Introductionmentioning
confidence: 99%